Modelling the Economic Growth of an Islamic Economy - M. Ramzan Akhtar (International Institute of Islamic Thought, 1993)
In an Islamic economy economic growth is not an end in itself, but rather a means of promoting the citizenry's good life. Growth depends upon several factors, among them a consistent increase in the amount of physical goods and seMces produced over a given period of time. This is usually taken as an index of economic growth. Adopting the same index, this paper asks: What factor explains economic growth in an Islamic economy? For this purpose, the paper refers to the Islamic economy of Madinah, which saw substantial expansion in all directions during the reigns of the Prophet and his four immediate political successols. This paper gives an answer based on the hypothesis that both physical and moral factors are instrumental in causing economic growth in an Islamic economy. This hypothesis is quite different from that of secular economics, which views economic growth only in terms of physical factors. Such an explanation has been found inadequate, however, as empirical studies on American data have shown that just over half of all output growth is explained by physical factors. Denison calls the unexplained part "the measm of our ignorance" (Branson and Litvack 1981). Many Muslim economists have discussed the role of moral factors in various forms (i.e., integrity, cultural will, and calls to the Muslim masses to regain their past glory). This paper, however, views the role of moral factors in terms of the bounty of God (fadl Allah). It is argued that this factor influenced economic growth through both autonomous and induced channels operating in institutional factors (i.e., the mosque and the state) and the level of God-consciousness (taqwa) in an Islamic society. The hypothesis is examined theoretically, because statistical data for empirical analysis is not available. The paper relies on the Qur'an and the ...